2013
DOI: 10.3109/07853890.2013.792495
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of self-ligands for activating natural killer cell receptors

Abstract: Natural killer (NK) cells are able to lyse infected and tumor cells while sparing healthy cells. Recognition of diseased cells by NK cells is governed by several activating and inhibitory receptors. We review numerous pathways that have been implicated in the regulation of self-ligands for activating receptors, including NKG2D, DNAM-1, LFA-1, NKp30, NKp44, NKp46, NKp65, and NKp80 found on NK cells and some T cells. Understanding how the regulation of self-encoded ligand expression is regulated may provide nove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 195 publications
0
23
0
Order By: Relevance
“…In both studies, NK cells were stimulated with cytokines for 48 h and further cultured for 18 h with cytokines in the absence or presence of ␣7 nAChR agonist or antagonist. To assess NKG2D-dependent cytotoxicity, we used a mouse urothelial carcinoma cell (MB49) transduced to stably express MICA on the cell surface (one of the known ligands for NKG2D (36,37)) or its corresponding negative control transduced with empty vector as target cells (Fig. 6A).…”
Section: Resultsmentioning
confidence: 99%
“…In both studies, NK cells were stimulated with cytokines for 48 h and further cultured for 18 h with cytokines in the absence or presence of ␣7 nAChR agonist or antagonist. To assess NKG2D-dependent cytotoxicity, we used a mouse urothelial carcinoma cell (MB49) transduced to stably express MICA on the cell surface (one of the known ligands for NKG2D (36,37)) or its corresponding negative control transduced with empty vector as target cells (Fig. 6A).…”
Section: Resultsmentioning
confidence: 99%
“…A variety of NK activating receptors are involved in recognition of virus-infected cells (18,(21)(22)(23)(24)(25)(26). One of the important NK activating receptors is DNAX accessory molecule 1 (DNAM-1), which binds to CD112 (nectin-2) and CD155 (poliovirus receptor, PVR), whose expression can be induced in both virus infected and tumor cells (5,(26)(27)(28).…”
mentioning
confidence: 99%
“…It is believed that TLR agonists enhance the efficacy of conventional cancer treatment by promoting the ability of dendritic cells to induce tumor-specific immune responses (5). We previously found that genotoxic anticancer agents induce the expression of immunomodulatory molecules including ligands for NKG2D, DNAM-1, and LFA-1 (12). Similarly, TLR agonists induce the expression of immunomodulatory molecules, some of which overlap with molecules induced in response to genotoxic agents (4,18,19).…”
Section: Ara-c and Pam 3 Csk 4 Treatment Reduces The Tumorigenicity Omentioning
confidence: 99%
“…Engagement of DNAM-1 and NKG2D by their respective ligands activate NK cells (12). On CD8 þ T cells, NKG2D and DNAM-1 trigger costimulatory signals, which enhance T-cell responsiveness.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation